Survey Manajemen Pembinaan Prestasi Cabang Olahraga Atletik di Kabupaten Kebumen (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this Study is to analyze the stages of the development achievements of the athletes PASI Kebumen on (1) Organization, (2) the Implementation of Coaching (3) Human Resources, (4)) the implementation of the exercise program , (5) facilities and infrastructure, (6) funding, and (7) the achievement data. The research method using descriptive qualitative. Method of data collection by observation, interview, and documentation. The subject of this research is to the board, coaches, and athletes. The data analysis technique used is the technique of triangulation of data. Data analysis with data collection, data reduction, data presentation, and conclusion of the data. The research results obtained, namely (1) the organization is structured, but in execution is not good, (2) the implementation of the coaching already organized and pretty good, (3) human resources ranging from the coach and the athlete is good enough, (4) exercise program that is made is good enough, (5) facilities and infrastructure owned inadequate and not standard, (6) funding obtained from the grant funds Kabupaten Kebumen, and (7) the achievements increased and continue to increase the bias is arguably already better.